Asymmetries and relationships between muscle strength, proprioception, biomechanics, and postural stability in patients with unilateral knee osteoarthritis - Zeng, Ziquan; Shan, Jiaxin; Zhang, Yilong; Wang, Yi; Li, Congcong; Li, Junyi; Chen, Weijian; Ye, Zixuan; Ye, Xiangling; Chen, Zehua; Wu, Zugui; Zhao, Chuanxi; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The pathological mechanism of knee osteoarthritis (KOA) is unknown. KOA degeneration may be associated with changes in muscle strength, proprioception, biomechanics, and postural stability. Objective: This study aimed to assess asymmetries in muscle strength, proprioception, biomechanics, and postural stability of bilateral lower limbs in patients with unilateral KOA and healthy controls and analyze correlations between KOA and these parameters. Methods: A total of 50 patients with unilateral KOA and 50 healthy subjects were recruited as study participants. Muscle strength, proprioception, femorotibial angle (FTA), femoral condylar–tibial plateau angle (FCTP), average trajectory error (ATE), and center of pressure (COP) sways areas were accessed in study participants, and the correlation between these variables was investigated. Results: In patients with unilateral KOA, lower limb muscle strength was significantly lower on the symptomatic side than on the asymptomatic side (p < 0.01), while the proprioception (degree error), FTA, FCTP, and ATE were substantially higher compared to the asymptomatic side (p < 0.01). However, no significant difference was observed in the healthy controls (p > 0.05). Patients with unilateral KOA had lower muscle strength than healthy controls (p < 0.05), but their proprioception (degree error), ATE, and COP sway areas were higher (p < 0.05). Muscle strength was found to be negatively correlated with ATE and COP sways areas (p < 0.05), whereas proprioception (degree error) was positively correlated with ATE and COP sways areas (p < 0.05) in all study participants. However, no correlation was found between FTA, FCTP, and ATE, COP sways areas in patients with unilateral KOA (p > 0.05). Conclusion: In patients with unilateral KOA, muscle strength, proprioception, biomechanics, and postural stability of bilateral limbs are asymmetrical in unilateral KOA patients. Muscle strength, proprioception, and postural stability are significantly associated variables, and changes in these variables should be considered in KOA prevention and rehabilitation.